Pengaruh Komitmen Organisasi dan Kecerdasan Emosional Terhadap Karyawan Serta Kepuasan Kerja Sebagai Variabel Mediasi - Arasy Ayu Setiamy; Muhammad Fauzan Azhmy; Maranata Kevin Tampubolon (Forum Kerjasama Pendidikan Tinggi, 2024)
Human resources is the improvement of human resources whose ability to complete the arrangement of human assets, execution, registration, preparation, improvement of the call of representatives or workers and take the impetus towards the authoritative advancement of an association or organization. Purpose to determine the effect of organizational commitment and emotional intelligence on Employee Performance through Job Satisfaction. The type of research used is quantitative research. The sample technique used is a saturated sample, namely all employees in the Human Resources Development Agency of North Sumatra Province (BPSDM) totaling 100 employees. Research Data Collection Techniques using questionnaires. The results showed organizational commitment and emotional intelligence had a positive and significant effect on job satisfaction, and organizational commitment and emotional intelligence had a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on performance, but job satisfaction is not able to mediate organizational commitment and emotional intelligence to employee performance.